The relationship between parental social support and emotion regulation among final-year college students - Sabilla Rafiana Puspitadewi; Desi Maulia; Ismah Ismah (Journal of Counseling, Education and Society, 2026)
Final-year students often face academic and emotional pressure while completing their thesis, making emotion regulation essential. This study examined the relationship between parental social support and emotion regulation among 205 final-year PGSD students at Universitas PGRI Semarang, selected via proportionate stratified random sampling (N = 420). A correlational design was used, with data collected through a 24-item self-developed parental social support scale and a 30-item emotion regulation scale based on Sarafino and Smith (2011) and Gratz and Roemer (2004), yielding Cronbach's Alpha of 0.911 and 0.877. Assumption tests were satisfied prior to Pearson product-moment correlation analysis. Results showed a positive and significant relationship between the two variables (r = 0.412, p < 0.001), with parental social support accounting for 17% of the variance in emotion regulation. These findings suggest parental social support may contribute to students' emotional stability during thesis completion, alongside other factors not examined in this study.